Comparing Orthodontist, Prosthodontist, Dental and Non-Dental Student Views on the Impact of Buccal Corridor on Smile Attractiveness of Women with Different Face Shapes - Afsari, Erfaneh; Niksolat, Elmira; Sadeghi rad, Sanam; Moshajari, Ali; Kazem Nezhad, Ehsan (Journal of Dental School, 2019)
Objectives Today, creating a balanced and attractive smile is the main goal of treatment in modern orthodontics. The buccal corridor is one of the controversial aspects of the smile attractiveness. The aim of this study was to compare the impact of buccal corridor on smile attractiveness of women with Mesoprosopic, Leptoprosopic, and Euryprosopic face types, from the perspective of orthodontists, prosthodontists, Dental and non-dental students. Methods In this comparative cross-sectional study, Photos were taken from 3 women with different face types and by making some changes in these photos, 5 buccal corridors (2%, 10%, 15%, 22%and 28%) were created for each one. Eventually, in order to survey, each 15 pictures were provided to individuals in the study group. Statistical analysis was performed by SPSS21 software, using K-S (Kolmogorov-Smirnov), Kruskal Wallis and Mann Whitney tests.p-value<0.05 was considered significant. Results Orthodontist and non-dental students considered that nearly wide smile for leptoprosopic face shape and wide smile with the minimum buccal corridor for variety of mesoprosopic and euryprosopic face shapes have the most attractiveness (p<0.05). Prosthodontists considered wide and narrow smiles as the least attractive regarding all types of faces (p<0.05). Conclusion Face shapes did not have a significant impact on the selection of the most attractive smile by prosthodontists, while orthodontists and non-dental students shared a similar view on the selection of the most attractive smile regarding the face shape.